Implementasi Nilai-Nilai Moderasi Beragama dalam Pembelajaran Pendidikan Agama Islam dan Budi Pekerti di SMK Citra Bangsa Mandiri Purwokerto - Fuzi Rahayu, Anteng; Ariyani, Dewi (Jurnal Pendidikan Agama Islam, 2025)
This research is motivated by the rampant cases of intolerance and radicalism that have spread in the world of education. Therefore, education, especially Islamic Religious Education, has a crucial role in promoting the values ​​of religious moderation. The purpose of this study is to analyze the implementation of the values ​​of religious moderation in Islamic Religious Education and Character Education learning at SMK Citra Bangsa Mandiri Purwokerto. This study uses a descriptive qualitative field research method with the research subjects being the principal, Islamic Religious Education & Guidance teachers, and class X students. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that teachers and class X students have implemented the values ​​of religious moderation in Islamic Religious Education and Character Education learning, including: 1. Tawassuṭ, including the habituation of holy book literacy, integration in Islamic Religious Education & Guidance learning. 2. I‘tidāl, including proportional and objective teacher assessment, through learning methods. 3. Tasamuh, including interactions between students and with teachers, the use of group work methods, and equal treatment of teachers towards all students. 4. Syura, includes the existence of rules before starting the lesson. 5. Qudwah, includes good teacher speech and behavior. 6. Muwaṭanah, includes the morning assembly. 7. I’tiraf al-‘urf, includes contextualization in the explanation of PAI & BP materials, there is no compulsion for non-Muslim students to wear the hijab